2018
DOI: 10.2134/jeq2018.05.0198
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Modeling of Pesticide Aquatic Exposures in California's Agricultural Receiving Waters

Abstract: For the aquatic exposure assessment of pesticides, the USEPA uses the Variable Volume Water Model (VVWM) to predict the estimated environmental concentrations (EECs) of a pesticide in a water body that receives runoff inputs from the Pesticide Root Zone Model (PRZM). The standard farm pond and additional generalized static and flowing water bodies used in endangered species assessment (aquatic bins) are used by USEPA to model the worst‐case aquatic exposure for the nationwide exposure assessment. However, whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The selection of PWC as the modelling software was based on a number of characteristics: (i) PWC is freely available online, (ii) it is versatile and allows the introduction of a large number of locally -or regionally-specific parameter values, (iii) it is widely used for North American pesticide regulation and registration. Although studies using PWC have previously been published in the literature (Xie et al 2018, Hatz et al 2019, Rumschlag et al, 2019, we are not aware that any sensitivity analysis has previously been performed for PWC, for either input values from the Pampa region or elsewhere. In this context, the objective of the current study was to perform a model-based sensitivity analysis of PWC for the Pampa Region of Argentina.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of PWC as the modelling software was based on a number of characteristics: (i) PWC is freely available online, (ii) it is versatile and allows the introduction of a large number of locally -or regionally-specific parameter values, (iii) it is widely used for North American pesticide regulation and registration. Although studies using PWC have previously been published in the literature (Xie et al 2018, Hatz et al 2019, Rumschlag et al, 2019, we are not aware that any sensitivity analysis has previously been performed for PWC, for either input values from the Pampa region or elsewhere. In this context, the objective of the current study was to perform a model-based sensitivity analysis of PWC for the Pampa Region of Argentina.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Mathematical models are now widely used in many countries to predict the transport and fate of pesticides in the environment (Teklu et al 2015, Gagnon et al 2016, Ouyang et al 2017, Hartz et al 2017, Bach et al 2017, Xie et al 2018, Rumschlag et al, 2019. Modelling represents an attractive alternative to environmental monitoring, which is expensive and time-consuming, and may sometimes be imprecise, as results depend on sampling frequency, and spatial and temporal variability (Bundschuh et al, 2014;Nsibande et al, 2015;Lorenz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical classes considered include pesticides, pharmaceuticals, an anti-bacterial agent and a flame retardant. To highlight key module attributes for predicting environmental exposure, we compare OrganoFate to the current model that USEPA uses to screen pesticides during registration, the Pesticides in Water Calculator (PWC) 2.0 model, (USEPA; Xie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While the PWC has been demonstrated to have general agreement with field observations (Xie et al, 2018), the model has several limitations for screening chemical exposure within the environment relative to OrganoFate. Within the PWC framework, users can only consider non-ionizable organic pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Padilla, Winchell, and Jackson () compared VVWM predictions with observed pyrethroid concentrations in outdoor mesocosms using the custom water body CVol conceptual model. Xie, Luo, Singhasemanon, and Goh () evaluated VVWM performance using CVol (standard farm pond, ESA static habitats) and CVO (ESA flowing habitats) conceptual models by comparing the 90th percentile annual maximum observed concentrations at the worst‐case agricultural receiving water body (small ditches or streams) for seven selected pesticides. They found that the CVol farm pond conceptual model was relevant to the most vulnerable water bodies in agricultural areas in California.…”
Section: Introductionmentioning
confidence: 99%